The Influence of Social Media on the Political Participation of Beginner Voters in the 2024 Presidential Election in Padang City - Devi, Yasinta; Adnan, M. Fachri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was conducted based on the high use of social media by people from all groups, small to large. This is used by politicians and presidential and vice presidential candidates as a campaign strategy. However, not all of them are used to access political activities and are vulnerable to exposure to hoax news that cannot be accounted for. This research aims to determine the influence of social media on the political participation of novice voters in the 2024 presidential election in Padang City. The research location is in Padang City, and the methodology approach is quantitative with 100 respondents using the Multistage Random Sampling technique from the research population consisting of first-time voters aged 17-20 years. The data was processed using a simple regression analysis method. Based on research results, social media has an influence on the political participation of first-time voters in the 2024 presidential election in the city of Padang by 38%.